Lower Limb Ground Reaction Force and Center of Pressure Asymmetry During Bodyweight Squats - Kelci B. Hannan; Adam C. King (North American Sports Medicine Institute, 2022)
# Background Performance asymmetries between the lower limbs have been reported across a variety of variables and for numerous motor tasks including double leg squats. Additionally, the degree of symmetry is often used as a recovery metric during rehabilitation programs. # Hypothesis/Purpose The purpose of this investigation was to examine leg asymmetry during a bodyweight double leg squat task and assess the effects of squat speed in a physically active population. # Study Design Cross-over Study Design. # Methods Eighteen healthy individuals completed two sets of 20 squats at two tempos (preferred tempo and 60 bpm) while ground reaction force and center of pressure data were recorded using dual force plates. Peak vertical ground reaction force, force impulse, and center of pressure (COP) standard deviation in the anterior-posterior (AP) and mediolateral (ML) direction were calculated and analyzed to identify any differences between legs, tempo, and as a function of repetitions. Significance was set at *ρ* ≤ .05. # Results The subjects exhibited greater ground reaction forces during the self-paced tempo compared to the metronome-paced tempo (*F*~1,79~ = 14.48, *p* \< .001) with the preferred leg generating larger values than the non-preferred leg during the self-paced condition. There was also a significant tempo x leg interaction for force impulse (*F*~1,79~ = 5.927, *p =* 0.015). A greater amount of COP variability was found in the preferred leg compared to the non-preferred leg in both the AP (*F*~1,79~ = 30.147, *p* \< 0.001) and ML (*F*~1,79~ = 41.204, *p* \< 0.001) directions. # Conclusions These findings highlight the importance of considering multiple levels of analysis when assessing lower limb symmetry as separate variables may provide differential evidence for asymmetry. Practically, these results emphasize the need for coaches and practitioners to consider different degrees of lower limb asymmetries that may impact the development and design of strength and rehabilitation programs. # Level of Evidence 3